2020
DOI: 10.1101/2020.10.27.358259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 desensitizes host cells to interferon through inhibition of the JAK-STAT pathway

Abstract: SARS-CoV-2 can infect multiple organs, including lung, intestine, kidney, heart, liver, and brain. The molecular details of how the virus navigates through diverse cellular environments and establishes replication are poorly defined. Here, we performed global proteomic analysis of the virus-host interface in a newly established panel of phenotypically diverse, SARS-CoV-2-infectable human cell lines representing different body organs. This revealed universal inhibition of interferon signaling across cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…It has been almost eighteen years since the advent of SARS-CoV as a member of the coronavirus in Guangdong, China (Walls et al, 2020 ). In 2012, Middle-East respiratory syndrome coronavirus (MERS), as another member of coronaviruses, caused the second pandemic of coronaviruses with a prevalence in 27 countries (Chen, 2020 ). HCoVHKU1, HCoV-229E, HCoV-OC43, and HCoV-NL63 are other coronaviruses that can infect humans, and their pathogenic role has been confirmed (Vinayagam & Sattu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been almost eighteen years since the advent of SARS-CoV as a member of the coronavirus in Guangdong, China (Walls et al, 2020 ). In 2012, Middle-East respiratory syndrome coronavirus (MERS), as another member of coronaviruses, caused the second pandemic of coronaviruses with a prevalence in 27 countries (Chen, 2020 ). HCoVHKU1, HCoV-229E, HCoV-OC43, and HCoV-NL63 are other coronaviruses that can infect humans, and their pathogenic role has been confirmed (Vinayagam & Sattu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus could affect various vital organs of human especially who has suffered from underling diseases; however, the many pathophysiological pathways of it remain unclear. In addition, mutation and changes in the structure of coronavirus could also consider as other obstacles to finding proper treatment against it (Cao et al, 2020 ; Chen, 2020 ; Cîrstea et al, 2020 ; Vinayagam & Sattu, 2020 ; Walls et al, 2020 ). Among the proposed molecular targets, 3CLpro (Main protease), PLpro (Papin-like protease), RdRp (RNA-dependent RNA polymerase) are main candidates for SARS-CoV-2 inhibition (Morse et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of COVID-19 patients with IFNs has not been approved yet. In general, SARS-CoV-2 infection modulates and inhibits the IFN response (Chen et al, 2020a, Konno et al, 2020, Lei et al, 2020). Moreover, it was recently shown that the host cell entry receptor ACE2 is indeed an ISG, and it was speculated that SARS-CoV-2 may exploit the IFN-driven upregulation of ACE2 to enhance infection (Ziegler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 replication seems to modulate and inhibit the interferon (IFN) response in infected target cells (Chen et al, 2020a, Konno et al, 2020, Lei et al, 2020). Still, it was also shown to be susceptible to inhibition by exogenously added IFNs in vitro (Busnadiego et al, 2020, Felgenhauer et al, 2020), in vivo (Hoagland et al, 2021) and in clinical trials (Monk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another short isoform of ACE2 expressed in the airway epithelium was also found to be upregulated by IFN stimulation and by infection with rhinovirus, but not with SARS-CoV-2 [ 229 , 230 ]. Furthermore, COVID-19 displays a profile of early IFN inhibition [ 231 ], and IFNs may not be significantly induced or even inhibited by SARS-CoV-2 in the lungs, thus possibly hindering the pattern of ACE2 upregulation during host antiviral response [ 232 , 233 ]. In line with these findings, in nasopharyngeal swabs of COVID-19 patients, decreased soluble ACE2 activity and ACE2 gene expression but increased expression of IFN stimulation genes were reported [ 234 ], suggesting the existence of IFN-independent mechanisms whereby SARS-CoV-2 suppresses ACE2 expression and function.…”
Section: Low Levels Of Lung Expression Of Ace2 and Accessory Proteinsmentioning
confidence: 99%